Diamonds as an investment option - Shun, Herman Han-Ming (2013)
This paper aims to explore the diamonds investment industry and how diamonds fare as a hedge against inflation. Firstly, an examination of the various efforts undertaken by certain organizations in improving the diamonds investment industry is carried out to better understand the current operating environment. Following that, the first part of the data analysis will include a comparative analysis of the risk-return characteristics of diamonds and gold. The results of the empirical study show that diamonds are not a good single-asset investment, as compared to other commodities such as gold. Subsequently, when an optimal risky portfolio consisting of diamonds and gold is evaluated, the findings show that there are potential diversification benefits when diamonds are held in a portfolio. Thereafter, a recommendation of the optimal investment option will be provided with respect to varying risk tolerance levels of different investors. Additionally, in analyzing diamonds’ price performance against inflation, it is noted that similar to gold, diamonds is not a good hedge against inflationary pressures.